A profile of lung cancer in the young population with a highlight on the Indian perspective - Tansir, Ghazal; Sharma, Aparna; Khurana, Sachin; Pushpam, Deepam; Malik, Prabhat Singh (Frontiers in Oncology, 2025)
Non-small cell lung cancer (NSCLC) is a disease primarily of the elderly, with a small proportion of patients in the younger age group. This subgroup of younger patients accounts for 1-10% among the Asian population and 2% in Caucasians. While variable age cut-offs have been taken for studies among these patients, there is sparse knowledge about the unique predisposing factors and etiology of lung cancer arising in them. Prior studies suggest that genetic factors, including Mendelian inheritance patterns and germline mutations, may contribute to early-onset lung cancer. Additionally, shorter durations of tobacco exposure in younger patients raise questions about alternative etiologies. Thus, there is potential for further research into the role of pathogenic germline mutations such as of the BRCA1, BRCA2 and TP53 genes. The higher prevalence of targetable genomic alterations such as EGFR mutations, ALK and ROS1 fusions in the young, and the lower proportion of BRAF, KRAS and MET alterations has therapeutic implications. Therapeutic outcomes among younger patients with lung cancer in localized and metastatic settings in real-world studies have been shown to be better than their older counterparts. It is notable that very young patients (less than 30 years of age) may have worse biology than those a decade older. Clinical trials assessing targeted treatments with tyrosine kinase inhibitors demonstrated equivalent results across age subgroups but representation of younger patients is disproportionate. Survival outcomes with immunotherapy for advanced lung cancer have shown the most improvement in those aged less than 55 years. Hence, treatment outcomes remain a subject of interest within this specific population, along with the issues of fertility, cancer treatment during pregnancy, financial toxicity and psychosocial counseling. There is paucity of literature on young Indian patients with lung cancer despite them presenting a decade earlier than the global population. Further studies are needed focusing on driving mutations, genetic, environmental and demographic factors influencing the presentation and treatment outcomes among Indian patients. This review focuses on the knowledge that exists and that which needs to be generated on these issues on young patients with lung cancer, with a spotlight on the Indian setting.